2020
DOI: 10.1111/cea.13706
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Ara h 6 as a marker of peanut protein absorption in tolerant and allergic humans following ingestion of peanut‐containing foods

Abstract: Background Bioaccessibility of food allergens may be a key determinant of allergic reactions. Objective To develop a protocol allowing the detection of the major peanut allergen, Ara h 6, in the bloodstream following ingestion of low amounts of peanut and to compare Ara h 6 bioaccessibility by food matrix. We further assessed for differences in absorption in healthy versus peanut‐allergic volunteers. Methods A blood pretreatment combining acidic shock and thermal treatment was developed. This protocol was then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 51 publications
(59 reference statements)
0
12
0
Order By: Relevance
“…4 The detection of food proteins in serum following consumption is challenging. 5 Nonetheless, we have previously reported that absorption kinetics for peanut are significantly different in peanut-allergic volunteers compared with nonallergic controls (Fig 1). For any given dose of peanut ingestion, there is higher Ara h 6 detection in serum samples from peanut-allergic individuals compared with controls, and peanut can be detected in the blood after much lower levels of ingestion, compared with controls.…”
mentioning
confidence: 81%
“…4 The detection of food proteins in serum following consumption is challenging. 5 Nonetheless, we have previously reported that absorption kinetics for peanut are significantly different in peanut-allergic volunteers compared with nonallergic controls (Fig 1). For any given dose of peanut ingestion, there is higher Ara h 6 detection in serum samples from peanut-allergic individuals compared with controls, and peanut can be detected in the blood after much lower levels of ingestion, compared with controls.…”
mentioning
confidence: 81%
“…This coincided with a number of studies evaluating the burden of peanut allergy and calling for improved protection for people with food allergy 69‐71 . Investigation of component IgE as a marker for ingestion, an immunological target and a discriminator with added diagnostic value also continues to be a busy area of science 72‐79 . Characteristics of infant food anaphylaxis were defined in one of the most extensive published series—hives, hypotonia and hypotension were common features in a French series with 61 infant cases, compared with 386 cases in preschool children 80 .…”
Section: Food Allergymentioning
confidence: 98%
“…Furthermore, digestion products of peanut 2S albumins yield a large and a small subunit (5 and 9 kDa) that remain associated by disulfide bridges so that the resulting heterodimer is as immunoreactive as the intact protein. Hence, immunoreactive Ara h 2 and Ara h 6 can be still detected and quantified in the bloodstream and in breast milk of non-peanut allergic human volunteers after peanut consumption or in the blood of peanut allergic patients after oral food challenge (61). These proteins have been shown to bind IgE and to be active in functional assays with RBL SX-38 cells (60,(62)(63)(64)(65)(66).…”
Section: The Contribution Of Physical Stability and Structure To Effe...mentioning
confidence: 99%